The epidemiology and mortality of pretibial lacerations. Issue 5 (May 2015) - Cahill, K.C.; Gilleard, O.; Weir, A.; Cubison, T.C.S.
Summary Pretibial lacerations are common injuries which have an underestimated mortality associated with their occurrence, and an under-appreciated morbidity associated with their treatment – they account for 5.2 out of every 1000 Emergency Department attendances in the United Kingdom, and occur mostly in the elderly. They are also increasingly being referred to plastic surgery units – the authors' department saw an increase from 58 referrals in twelve months in 2005/2006 to 113 referrals in six months in 2011. The Queen Victoria Hospital, East Grinstead, follows an evidence based and multi-disciplinary practice for the treatment of these injuries. The authors present the outcomes of patients referred to the hospital from the community and treated according to these guidelines, and compares the outcomes and mortality to a period prior to the introduction of this practise. The average time for skin grafted wounds to heal is found to be 59.8 days and for the donors it is 50.3 days, compared with an average time to healing of 123 days for those managed conservatively. The one month and one year mortality associated with these injuries is highlighted, as is the reduction in these figures following the adherence to the current treatment regime – prior to its introduction the 31 day mortality was 15%, and this was reduced to 4.3% by achievable changes in practice and treatment. Finally, the relevant extant research literature regarding pretibial lacerations is reviewed.